2020
DOI: 10.3389/fenvs.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanoplastic Exposure Effects in Microalgae: A Meta-Analysis of Standard Growth Inhibition Tests

Abstract: Background: Ecological impacts of micro-and nanoplastics particles (MNP) are among the most discussed environmental concerns. In algae, MNP are commonly hypothesized to reduce growth, which is a standard ecotoxicological endpoint. However, the reported test outcomes vary, with both growth inhibition and stimulation being observed. Due to this conflict of information, a data synthesis for MNP potential to cause growth inhibition in toxicity testing is needed. Methods: We performed a meta-analysis study to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 74 publications
(122 reference statements)
0
23
0
Order By: Relevance
“…Current test methods in ecotoxicology are intended for soluble (at least partially) chemicals, whereas testing particle suspensions, such as microplastic, requires different approaches (Paul-Pont et al, 2018;Gerdes et al, 2019). Moreover, plastics are diverse: they represent different polymers and materials that include a broad array of chemical additives and come in many sizes, colors, and shapes (Rochman et al, 2019), which complicates comparisons between the effect studies (Reichelt and Gorokhova, 2020). It is also essential to keep in mind that plastic is only a kind of persistent solid waste pollution, and common approaches for the risk assessment are needed (Coe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current test methods in ecotoxicology are intended for soluble (at least partially) chemicals, whereas testing particle suspensions, such as microplastic, requires different approaches (Paul-Pont et al, 2018;Gerdes et al, 2019). Moreover, plastics are diverse: they represent different polymers and materials that include a broad array of chemical additives and come in many sizes, colors, and shapes (Rochman et al, 2019), which complicates comparisons between the effect studies (Reichelt and Gorokhova, 2020). It is also essential to keep in mind that plastic is only a kind of persistent solid waste pollution, and common approaches for the risk assessment are needed (Coe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite environmental health concerns, only a few studies have shown consistent adverse effects of microplastics (Foley et al, 2018;Reichelt and Gorokhova, 2020), usually observed at very high microplastic concentrations. As a rule, these concentrations exceed levels that are recognized as environmentally relevant (Lenz et al, 2016;Phuong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations